Tinjauan Kepuasan Pasien dari Dimensi Mutu Pelayanan Makanan di Ruang Rawat Inap Kelas III Rumah Sakit Bahteramas Provinsi Sulawesi Tenggara - Roestam, Aulia Caprina; Nurlela, Euis (Jurnal Gizi Ilmiah, 2016)
Nutrition services as one of the health services that become a benchmark for service quality in hospitals because food is a basic human need and is highly believed to be a factor in preventing and curing a disease. Nutrition service activities include food procurement, nutritional care for inpatients and outpatients, nutrition consultation and referrals as well as applied nutrition research. This study aims to determine patient satisfaction from the dimensions of food service quality in class III inpatient rooms at Bahteramas Hospital, Southeast Sulawesi Province. This research is a descriptive study with a survey approach and was carried out on February 4-15, 2016 at Bahteramas Hospital, Southeast Sulawesi Province. The sample used in this study was 63 people. The sampling technique used is purposive sampling. This study shows that of the 63 samples, most of the food service satisfaction is 60 people (95.2%) in the satisfied category and the rest are 3 people (4.8%) in the dissatisfied category. Then from the reliability dimension, most of them are 49 people (77.8%) in the satisfied category, the responsiveness dimension is mostly 49 people (77.8%) in the satisfied category, the guarantee dimension is mostly 50 people (79.4%) in the satisfied category, then on the empathy dimension most of them are 52 people (82.5%) in the satisfied category and on the physical evidence dimension most of them are 42 people (66.7%) in the satisfied category. For other researchers, they should examine Other variables that have not been studied are related to the quality of service (menu variations, ways of serving food, timeliness of serving food, condition of the place and eating utensils, attitudes and behavior of officers who serve food) at Bahteramas Hospital, Southeast Sulawesi Province.